An assessment on the job management module millenium falcon billing system - Rubia, Karlmarx T. (Quezon City University of the Philippines Diliman, 2006)
Innove Communications-Corporate Business Group provides relevant solutions for business customers on high-speed data services over a nationwide broadband network. Innove provides data services such as leased lines, IP-VPN, voice, video and satellite services both for international and domestic and internet service under the brand name of Globequest. In 2001, Corporate Business Group initiated the project to acquire a billing system that will support their existing services plus their upcoming expanded range of services that they will offer to the market. In their pursuit to institute a culture of service excellence and proactive challenger orientation, the Corporate Business Group initiated to replace the existing billing system. With the existing system limitations, the business was compelled to pursue the acquisition and implementation of an integrated system that would support the business in achieving its goals and objectives as follows : attract new and retain old customers through innovative and value-added product offerings. Respond immediately to new market opportunities and competitive threats. Provide fast and efficient service. Bill customers accurately. In 2003, Innove has commissioned Singapore Telecom (Singtel) to provide the integrated billing system to address the needs of the business. Singtel's proposal is to extend and customize existing CTABS functions and features to support GlobeQuest services. The system shall contain the following functionalities: 1. Customer Care and Order Processing. This module provides user with the means of capturing, progressing and maintaining details of customer's service requirements such as order taking and processing, account management, job management, product and services registry and negative database checking for credit control management. Customer Billing and Collection. This module consists of various invoicing and credit control facilities which provide a whole range of activities needed to bill customers for products, services and collection. Engineering. The system maintains exchange plant, network plant and equipment records. It allows individual items of plant and equipment be reserved and allocated for a particular purpose, assist engineers to administer the changes and enhancements to the network and record fault history for specific items. 4. Contact Management. This module which is not included in basic CTABS, is designed for Sales Personnel to keep track of contracts (prospect as well as existing accounts in the billing system). It links the entire business relationship history-meetings, calls, to do items, proposals, etc. It also interfaces to the billing system to convert prospect to existing account. It also interfaces to work flow system to manage the pre-sales process. 5. Interface with other applications/systems. The system is flexible for interfaces with other systems, provided that interface specification are clearly identified and agreed with the third party system. The system is also ready for any mediation device. The proponent provided an assessment on the Job Management Module of the Millennium Falcon Billing System. He conducted an in-dept analysis on how the new billing system affected the performance of the group in terms of end to end service delivery. This study will examine the current detailed functional specification (DFS) of the system. From the current DFS, the proponent will identify the system deviations from the original design and study the impact of such deviation on the overall performance of the group in delivering the services to the customers. Upon identification of the main issues related to the system, the proponent come up with his own DFS to be submitted to the MFalcon Developer to be implemented on Phase 2.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Business enterprises; Broadband communication systems